Kombinasi Trichokompos Tithonia dan Pupuk NPK dalam Meningkatkan Pertumbuhan dan Hasil Bawang Merah (Allium ascalonicum L.) - Ichwan, Budiyati; Lestari, Ardiyaningsih Puji; Eliyanti, Eliyanti; Zulkarnain, Zulkarnain; Arrahman, Rinza (Jurnal Media Pertanian, 2024)
The development and increase of shallot production in Ultisol dry land is hampered by its relatively low fertility.  Efforts that can be made are by adding organic material derived from plants such as Tithonia diversifolia (paitan/kipahit/insulin leaf) which is composted by adding trichoderma, to increase the soil's ability to hold water, increasing soil organic carbon,  soil nutrient availability, and  growth, and crop yields. The use of tithonia trichocompost as a soil ameliorant can not only increase soil fertility but also reduce the use of NPK fertilizer. This research aims to examine the effect of a combination of tithonia trichocompost and NPK fertilizer on the growth and yield of shallots.  Research location at Teaching and Research Farm, Faculty of Agriculture, Jambi University (35 m above sea level). The research used a Randomized Block Design with five combination treatments of tithonia trichocompost  and NPK fertilizer (percentage based on recommended dose), namely: 0% tithonia trichocompost + 100% NPK; 25% tithonia trichocompost + 75% NPK; 50%  tithonia trichocompost + 50% NPK; 75% tithonia  trichocompost  + 25% NPK; 100% tithonia trichocompost. The recommended dose used is 20 tonha-1 tithonia trichocompost and 400 kgha-1 NPK fertilizer (16:16:16). The research was repeated five times. The research results showed that various combinations of tithonia trichocompost and NPK fertilizer that were tried increased plant growth and yield, and as the percentage of tithonia trichocompost increased, plant growth and yield increased. 100% tithonia trichocompost gave the highest yield, 44.123 g per hill or 7.7 tons ha-1 (if land use efficiency was 70% with a plant spacing of 20 cm x 20 cm). Although this yield is lower than the potential yield of shallots, which is 9.5 tonha-1, the use tithonia trichocompost as a soil ameliorant can replace NPK fertilizer.Keywords: ameliorant, organic matter, Ultisol dry land, water avaibility